Defining workplace innovation: The Fifth Element. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – This paper aims to introduce the 'Fifth Element' as 'joint intelligence' shared by all stakeholders in the workplace and at the wider economic and social level, and aimed at closing the evidence-practice gap. Design/methodology/approach: – The mutually reinforcing impact of practices based on employee involvement and participation at all levels of an organisation can create a tangible effect in workplaces, which is hard to quantify but which is often described in terms of "culture" and "employee engagement". Findings: – The first four elements comprise Job Design and Work Organisation; Structures and Systems; Learning, Reflection and Innovation; and Workplace Partnership. When these combine successfully, the outcome can be remarkable producing a tangible and sustainable change in the day-to-day culture of an organization, which includes across the board improvements in communications, leadership and employee engagement, higher performance, enhanced customer care and a self-perpetuating regime of innovation. Originality/value: – The metaphor of the Fifth Element is a useful way of capturing this essence, describing an alchemic transformation that can only take place when the other four elements combine.